دور الإتصال الداخلي في تحسين العلاقة بين العمال دراسة ميدانية بمديرية الشباب والرياضة لولاية سوق أهراس - مرزوقي نجوة (My University, 2019)
Summary of the study: The problem of the role of internal communication in improving the relations between the workers of the Directorate of Youth and Sports of the State of Souk Ahras, to know if this role is positive because of the good use of the system of internal communication in all its forms and methods, means and networks, characteristics and functions, the improvement of relations between workers at all levels, or the negative character of this role due to the lack of good use of internal communication , improves the relationship between the workers, but on the contrary constitutes another obstacle to the improvement of the relationship between the workers and is therefore the main objective of the communication. The study must be aware of the role of internal communication in improving relationships between workers and a series of sub-objectives, the most important of which is to know the nature of communications between workers in management, as well as the role of official contacts in improving the relations between the workers within the management, as well as the nature of the relations within the management, On the relationship between the management workers, and to achieve these objectives was based on the descriptive and observation method and the form to collect data from the management staff under study using the full inventory method, ------------------- ملخص الدراسة: تتمحور إشكالية دور الاتصال الداخلي في تحسين العلاقات بين عمال مديرية الشباب والرياضة بولاية سوق أهراس، حول معرفة ما إذا كان هذا الدور إيجابيا نتيجة الاستخدام الجيد لمنظومة الاتصال الداخلي بكافة أشكاله وأساليبه ووسائله وشبكاته وخصائصه ووظائفه، وتحسين العلاقات بين العمال على جميع المستويات، أم أن هذا الدور سلبي نتيجة عدم الاستخدام الجيد للاتصال الداخلي، إذ يحسن العلاقة بين العمال، بل على العكس، يشكل عائقا آخر أمام تحسين العلاقة بين العمال، وبالتالي فهو الهدف الرئيسي من الاتصال. يجب أن تدرك الدراسة دور الاتصال الداخلي في تحسين العلاقات بين العاملين، وسلسلة من الأهداف الفرعية، من أهمها معرفة طبيعة الاتصالات بين العاملين في الإدارة، وكذلك دور الاتصالات الرسمية في تحسين العلاقات بين العاملين داخل الإدارة، وكذلك طبيعة العلاقات داخل الإدارة، والعلاقة بين العاملين في الإدارة، ولتحقيق هذه الأهداف تم الاعتماد على المنهج الوصفي والملاحظة، واستمارة لجمع البيانات من موظفي الإدارة محل الدراسة باستخدام أسلوب الحصر الكامل.
Keywords: الإتصال الداخلي، العمال